Synchronous synthesis of electro-exfoliated/oxidized binder-free expanded graphite paper at low potential for solid-state capacitor. (15th August 2022) - Bu, Qijing; Cao, Xiaoyan; Li, Shu; Bao, Jinpeng
Abstract: Expanded graphite paper has been applicable to capacitors favorably. However, due to its low electrochemical active area, this paper-type capacitive material usually needs to be further treated. In this paper, electro-exfoliation and electro-oxidation strategies are combined in one-step under low potential. The modified material has both porous structure and functional groups, which improves the electrochemical properties of the electrode obviously. The energy density and capacity retention rate of assembled solid-state capacitor can reach 13.6 mAh g −1 at 0.5A g −1 and 79.5% after cycling 5000 times, respectively. The potential of this synthetic strategy is further demonstrated by electrodepositing process. Graphical abstract: Unlabelled Image Highlights: Electro-exfoliated/oxidized expanded graphite paper is one step synthesized at low potential. The modified expanded graphite paper is suitable for both in positive and negative electrodes The potential of this synthetic strategy is further demonstrated by electrodepositing process.